Causal of road safety: A study among motorcyclists in Selangor / Farzana Izzati Abdullah ... [et al.] - Abdullah, Farzana Izzati; Ahmad, Yarina; Bakar, Ahmad Naqiyuddin; Jaafar, Harlina Suzana (2021)
Road traffic crashes are often to be heard. It is a long-standing issue in this world and Malaysia is no exception to this issue. This issue has been debated until now (Hoque, Rossen, & Tse, 2011; Parker, Allen, & Watson, 2016; Crash Countermeasures & Design of Safety, 2017; Musselwhite, 2018; Zhao, Li, Chen, Li, & Ding, 2021) and the outcomes still demonstrate increasing amount which has been attributed to road traffic crashes. Road traffic crashes are becoming a global issue around the world. Thus, it needs crucial attention from all parties to reduce the number of road traffic crashes. Road traffic crashes are one of the major contributors to the statistics of the leading cause of death in Malaysia. It shows road traffic crashes are the fourth highest of all other causes of death (Department of Statistics Malaysia, 2019). Based on the road traffic crashes statistics, the number of road user deaths due to road traffic crashes comes from the group of motorcyclists (Malaysian Road Safety Department, 2020). This can be proved when the Malaysian Road Safety Department revealed that motorcycles recorded the highest number of accidents with a total of 3959 cases compared to cars that recorded 1253 cases, followed by pedestrians with 394 cases and lorries recorded a total of 182 cases (Malaysian Road Safety Department, 2020). As can be seen, by the numbers recorded by the Malaysian Road Safety Department, this indicates that motorcyclists are most vulnerable to danger while riding on the road compared to cars that are less vulnerable to danger. This study aims to examine the factors (human factor, road condition, vehicle condition) contributing to road safety among motorcyclists.